Design of asynchronous quasi-delay-insensitive library cells and circuits for asynchronous microprocessors - Chin, Qi Lin. (2009)
This report presents the Design of Asynchronous Quasi-Delay-Insensitive Library Cells and Circuits for Asynchronous Microprocessors. Asynchronous are self-timed circuits that employ hand-shaking protocol. Quasi-Delay-Insensitive Library cells are circuits that do not assume any time delay to work properly. These circuits can be used to communicate with asynchronous microprocessors. This library cells can be used by IC designers when designing bigger and more complex circuitry in future. The technology used is 0.13µm IBM technology.